Low-gamma shift asymmetrical double-side blue-phase liquid crystal display. Issue 2 (26th January 2020) - Guo, Yuqiang; Li, Xiaoshuai; Yang, Yanling; Zhang, Chi; Sun, Yan; Zhang, Hui; Sun, Yubao
ABSTRACT: A single-domain blue-phase liquid crystal display (BPLCD), which has asymmetrical double-side electrode structure, is proposed to reduce gamma shift. Firstly, the electro-optical curve and gamma shift of the proposed BPLCD are discussed under the comparison with conventional in-plane switching (IPS) BPLCD. And then, its gamma shift is investigated under various conditions. Compared with the conventional IPS-BPLCD, the operating voltage can be reduced by ~31%, and the transmittance is increased by ~6%. The indistinguishable gamma shift can be obtained under various electrodes' sizes, when the cell gap is appropriate. The results also indicate that if the electrodes' height and Kerr constant of BPLC increase, the operating voltage can be further reduced (only 9.6 V in this work), and the gamma shift almost do not change. Moreover, a certain misalignment between the top and bottom glasses are permitted, which is good for reducing the fabrication difficulty. In terms of viewing angle, the proposed BPLCD has an average contrast ratio of ~5000:1, and the gamma shifts at full viewing angles are all indistinguishable. Graphical Abstract: uf0001